2017
DOI: 10.22159/ijpps.2017v9i6.16935
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation Kinetics of Kaempferol and Quercetin in the Pre-Formulated of the Standardized Extracts of Poincianella Pyramidalis (Tul.) L. P. Queiroz Obtained by Spray Dryer

Abstract: Objective: The aim of this work was to evaluate the stability and determine the kinetic parameters of degradation of biomarkers kaempferol and quercetin, present in the pre-formulated of the extract of Poincianella pyramidalis obtained by a spray dryer. Methods:A 2 3 experimental design coupled with RSM was applied to evaluate and optimize the effects of processing parameters on the content of chemical markers in dry extracts by a spray dryer. Stability testing was performed to verify the influence of temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…The effects of FIR heat energy on ginseng leaf flavonoids were assumed in two situations according to temperature variation: (1) The relatively fast deglycosylation of panasenoside accompanied by the slow degradation of kaempferol occurred when FIR temperatures were below 180 °C, which explains the relatively slow decrease in the panasenoside content and the sharp increase in kaempferol, and (2) the rapid deglycosylation of panasenoside accompanied with the faster degradation of kaempferol when the FIR temperature exceeded 180 °C, which explains the rapid decrease in panasenoside and the lack of significant change in the kaempferol content. These assumptions were supported by Oliveira et al [ 28 ]. They reported that the kaempferol content of Poincianella pyramidalis decreased significantly when the air inlet temperature was increased from 160 to 180 °C during spray-drying.…”
Section: Resultssupporting
confidence: 66%
“…The effects of FIR heat energy on ginseng leaf flavonoids were assumed in two situations according to temperature variation: (1) The relatively fast deglycosylation of panasenoside accompanied by the slow degradation of kaempferol occurred when FIR temperatures were below 180 °C, which explains the relatively slow decrease in the panasenoside content and the sharp increase in kaempferol, and (2) the rapid deglycosylation of panasenoside accompanied with the faster degradation of kaempferol when the FIR temperature exceeded 180 °C, which explains the rapid decrease in panasenoside and the lack of significant change in the kaempferol content. These assumptions were supported by Oliveira et al [ 28 ]. They reported that the kaempferol content of Poincianella pyramidalis decreased significantly when the air inlet temperature was increased from 160 to 180 °C during spray-drying.…”
Section: Resultssupporting
confidence: 66%
“…Thus far, the identified phenolic compounds in Moringa leaves consisted of kaempferol, quercetin, chlorogenic, caffeic, coumaric, ferulic, and gallic acid (Castillo‐López et al, ; Manguro & Lemmen, ). Some of these phenolic compounds were reported to be thermostable, for instance, the quercetin that could be retained up to 120°C (start to decrease at 150°C) and kaempferol that could be retained up to 160°C (start to decrease at 180°C) (Oliveira et al, ; Sharma et al, ).…”
Section: Resultsmentioning
confidence: 99%